1992
DOI: 10.1161/01.str.23.11.1551
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in stroke incidence and mortality. The Framingham Study.

Abstract: Background:The reduction in US stroke mortality has been attributed to declining stroke incidence. However, evidence is accumulating of a trend in declining stroke severity.Methods: We examined secular trends in stroke incidence, prevalence, and fatality in Framingham Study subjects aged 55-64 years in three successive decades beginning in 1953, 1963, and 1973.Results: No significant decline in overall stroke and transient ischemic attack incidence or prevalence occurred. In women, but not men, incidence of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
164
1
12

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(185 citation statements)
references
References 26 publications
8
164
1
12
Order By: Relevance
“…Indeed, advancing age is the single most important risk factor in stroke: in both men and women the stroke rate more than doubles for each successive 10 years after age 55 (Brown et al 1996;Wolf et al 1992).…”
Section: The Immune System and Strokementioning
confidence: 99%
“…Indeed, advancing age is the single most important risk factor in stroke: in both men and women the stroke rate more than doubles for each successive 10 years after age 55 (Brown et al 1996;Wolf et al 1992).…”
Section: The Immune System and Strokementioning
confidence: 99%
“…2,[4][5][6][7] Earlier studies concluded that the decline in stroke mortality was mainly, but not only, due to the decreased incidence of cerebrovascular complications linked to primary prevention measures, especially the detection and treatment of hypertension. Although there was no reduction evidenced in some developed nations, as shown in Table 1, [8][9][10][11][12][13][14][15][16][17][18][19][20] it may be speculated that hypertension treatment has contributed to the decline in stroke mortality, in particular by reducing the severity of acute stroke. 18 Better emergency medical care may also have led to a decrease in casefatality rate.…”
Section: Mortalitymentioning
confidence: 99%
“…Modifiable risk factors (see in Table 2) 23 have been extensively reviewed and the predominant role of hypertension is underlined by all the epidemiological studies. [23][24][25] Hypertension increases the risk for transient ischaemic attacks 26 as well as the incidence of any type of stroke 24 including ischaemic stroke and focal (Harmsen, 1992) 10 No change 1971-1987 Framingham Study 11 No change 1953-1983 New Zealand (Bonita et al, 1993) 12 No change 1981-1991 Hawai (Kagan, 1994) 13 Decrease 1969-1988 China (Cheng et al, 1995) 14 Decrease 1986-1990 East Germany (Eisenblätter, 1995) 15 Increase 1972-1980 Finland (Tuomilehto, 1996) 16 Decrease 1983-1992 Minnesota (Brown et al, 1996) 17 Increase 1950-1989 Portland (Barker et al, 1997) 18 No change 1967-1985 Minnesota (Shahar, 1997) 19 intracerebral haemorrhage. 27 Data from the Framingham Heart Study show that hypertensive subjects have a three-fold greater risk of stroke than normotensive individuals and those with borderline hypertension have a 50% greater risk.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of incidence must be based on data from communities such as Rochester, Minn, 3 or on ongoing cardiovascular disease cohort studies such as the Framingham Study. 4 Since 1966 the Honolulu Heart Program has monitored the incidence and mortality from CHD and stroke in a cohort of men of Japanese ancestry born from 1900 to 1919 and living on the island of Oahu, Hawaii. Questionnaires mailed to 11 136 of these men early in 1965 were answered by 9877 men.…”
mentioning
confidence: 99%